UNDERSTANDING MULTICULTURAL CONCEPTS IN SOCIAL STUDIES LEARNING THROUGH CANVA MEDIA - Tetep; Fauzi Fiqri Nugraha; Helsa Hanifah; Dianah, Lili (SAHUR Journal, 2025)
The background to the problem in this research is the importance of multicultural education in shaping students' understanding and attitudes towards cultural diversity in the era of globalization. However, the challenge of teaching this concept effectively and interestingly remains an obstacle in many schools. This research aims to examine the effect of using Canva-based poster media on understanding multicultural concepts in class VIII students at SMP Negeri 1 Garut. The research design used is a quantitative approach with a quasi-experimental method with a nonequivalent control group pre-test and post-test design to measure students' understanding before and after using the media. The sample consisted of two groups: an experimental group using Canva-based posters and a control group using Power Point media. Based on the results of the statistical analysis carried out, the initial abilities of the two groups resulted in the same abilities. Meanwhile, the final test results obtained a Sig.2-tailed value of 0.049 and an α of 0.05, meaning 0.049 < 0.05, so the HO was rejected. This shows a significant increase in understanding of multicultural concepts in the experimental class compared to the control class.